The Perception of Cia-Cia Tribe Students in Southeast Sulawesi Toward South Korea: The Case of Education Aid for Cia-Cia Language Preservation - Darynaufal Mulyaman; Asra Virgianita; Darang Sahdana Candra (Global Strategis, 2021)
Since the beginning of the "Korean Wave" in the 2010s, Korean language and the Hangeul alphabet are integral parts in the dissemination of South Korea's soft power across the world. For instances, the South Korean government provided support for the preservation of Cia-Cia language of Cia-Cia ethnic group in Bau-Bau, Southeast Sulawesi, Indonesia - a program that was originally initiated by Hunminjeongeum Society Foundation in 2008. This study examines the perception of students with Cia-Cia ethnic background toward South Korea. Questionnaire surveys and interviews are used to further look into their perceptions. This study, that started from a thesis, finds that the students who participated in the program have positive perceptions of South Korea. Furthermore, the demonstration of Korean culture and the use of Korean language become more apparent in the students’ daily life, creating a new social reality in the local community. Such finding suggests that international assistance has effectively become a part of South Korea's soft power expansion strategy.Keywords: Cia-Cia, Language, Foreign Aid, Korea, PerceptionSejak merebaknya "Korean Wave" pada dekade 2010-an, Bahasa Korea dan Aksara Hangeul adalah bagian integral dalam penyebaran soft power Korea Selatan di seluruh dunia. Pemerintah Korea Selatan, misalnya, memberikan dukungan untuk pelestarian bahasa Cia-Cia dari Suku Cia-Cia di Bau-Bau Sulawesi Tenggara, Indonesia - sebuah program yang awalnya diprakarsai oleh Yayasan Hunminjonggeum Society pada tahun 2008. Studi ini mengukur persepsi siswa dengan latar belakang etnis Cia-Cia terhadap Korea Selatan. Survei kuesioner dan wawancara digunakan untuk melihat lebih jauh persepsi mereka. Studi ini berangkat dari tesis yang dilakukan dan menemukan bahwa siswa-siswa yang terlibat dalam program tersebut memiliki persepsi yang positif tentang Korea Selatan. Selain itu, peragaan budaya Korea dan penggunaan Bahasa Korea menjadi lebih jelas dalam kehidupan sehari-hari siswa-siswa tersebut sehingga menciptakan realitas sosial baru di komunitas lokal. Temuan tersebut menunjukkan bahwa bantuan internasional dapat dan telah secara efektif digunakan sebagai strategi ekspansi soft power Korea Selatan. Kata-kata Kunci: Cia-Cia, Bahasa, Bantuan Luar Negeri, Korea, Persepsi